Sosialisasi dan Pendampingan Pengurusan PIRT sebagai Upaya Pengembangan Kualitas Usaha di Usaha Kue Kering Lala, Kelurahan Pisang Candi, Kecamatan Sukun Kota Malang - Purborini, Vivi Sylvia (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
UMKM can absorb labor and reduce unemployment in Indonesia. In the midst of the Covid-19 pandemic, many people are engaged in entrepreneurship according to their areas of interest and ability. This is proven by the many UMKM that emerged during the Covid-19 pandemic era. Business actors engaged in the food sector are required to have a distribution permit as well as guaranteeing the safety of the food products they sell. PIRT certificate or home industry food is a distribution license that must be owned by food industry business actors. According to initial interviews, the location of the lala cookies is in the Banana Candi sub-district, Sukun sub-district, Malang city, they don't have a PIRT, and they don't know about PIRT. The lack of knowledge of business legality, in this case PIRT, is one of the causes. Based on these problems, socialization and assistance in obtaining PIRT permits were held by lecturers at the Faculty of Law, Wisnuwardhana University, Malang. Methods of community service activities regarding PIRT socialization and Assistance in Making PIRT. This activity shows indicators of success, which can be seen from the enthusiasm of the socialization participants in the discussion, and the understanding of the importance of business legality, in this case the PIRT number, to increase knowledge of production feasibility and production development and how to increase production frequency and marketing reach of lala cookies.